(untitled) (Tanzania Medical Journal, 2020)
Background Sinonasal tumours are rare, with an annual incidence of approximately 1 case per 100,000 inhabitants worldwide. Despite their rarity, they cause deleterious effects especially in countries with limited access to health services. Broad objective This study aimed at determining the proportion, clinicopathological characteristics and stage at diagnosis of sinonasal tumours among patients attending Otorhinolaryngology department at Muhimbili National Hospital Dar es Salaam Tanzania. Methodology A hospital-based descriptive cross-sectional study was conducted among 6630 patients who attended Otorhinolaryngology department at Muhimbili National Hospital, which is the national referral hospital in Tanzania from June 2015 to February 2016. Structured questionnaire and clinical examination forms were used to interview the study participants. Computed tomography scan of the nose and paranasal sinuses and chest X-Ray were done to all patients with clinical presentation of sinonasal tumours and biopsy was done to confirm the diagnosis. Data analysis was done using Statistical Package for Social Science version 20. Results Of the 6630 study participants 38(0.57%) had histopathological confirmed sinonasal tumour. Among them 23(60.5%) were males with M: F ratio of 1.5:1. Their ages ranged from 9 to 87 years with a mean age of 47.63 ±19.7 years. Most patients 37 (97.4%) presented with rhinological features for sinonasal tumours. Of the 38 patients with sinonasal tumours, 30(78.9%) had malignant tumour and peak age of occurrence was 50 years and above 19(50%) followed by 30 to 39 years 8(21.1%). Squamous cell carcinoma was the most common histological type seen in 14(42.9%) patients followed by adenocarcinoma 4(13.3%). Inverted papilloma was the most common benign tumour accounting 6(62.5%) with peak age of occurrence at 50 years and above. All patients with malignant sinonasal tumours had stage III and IV disease. Among them, 6 (20%) had neck node metastasis to the level I and II and one had metastasis to the lungs. Conclusion and recommendation Malignant sinonasal tumours are the most predominant in our setting with male preponderance at the age of 50 years and above. Most patients presented with advanced disease, which warrant further studies to identify and address factors contributing to advanced stage at presentation. Keywords: Sinonasal, Tumours, Magnitude, Muhimbili National Hospital, Tanzania.